KEKUATAN SISI REFLEKSIF PADA GRAF RANTAI SEGITIGA - Wulan Indah Saputri; Diari Indiarti (UNEJ e-Proceeding, 2022)
Given a simple connected graph  with set of vertices is  and set of edge is . A graph  is called to have an edge irregular reflexive -labeling if each vertices can be labeled with an even positive integer  and each edge can be labeled with a positive integer  such that each edge has a different weight. The weight of an edge  on a graph  is the sum of the vertex label , vertex label , and  edge label. The reflexive edge strenght of a graph  denoted by  is the minimum  of the largest label in graph  with . In this paper, we determine the reflexive edge strenght of the triangular chain graph -path for . The reflexive edge strenght of the triangular chain graph -path is 3 for ,  for  is even and , and  for  is odd. Keywords: Edge irregular reflexive labeling, reflexive edge strenght, and triangular chain graph